Clinical and histopathological changes in rainbow trout Oncorhynchus mykiss experimentally infected with fungus Bradymyces oncorhynchi - Řehulka, J; Kolařík, M; Hubka, V (Folia microbiologica, 2020)
Bradymyces oncorhynchi is a poorly known melanised fungal species that has been isolated only from a hyperaemic focus near the enlarged spleen of a rainbow trout. Although the pathogenicity of this species to fish is suspected, it has not been fully confirmed. Four laboratory experiments were conducted to test the effect of the fungus on the health of rainbow trout fingerlings. Mycelia were cultivated under different conditions to increase inoculum variability and to test the impact of the conditions on the pathogenicity. The inoculum was subsequently administered by the intraperitoneal route. The clinical manifestations, gross pathological lesions and histopathological changes were identical in all experimental groups, i.e. lethargy, inappetence, anorexia, weight reduction, pale gills, full-thickness ulceration of the abdominal wall, muscle atrophy, haemorrhagic or pale liver, fat-altered pyloric region with haemorrhages, enlarged spleen, haemorrhagic ascites, systemic granulomatous lesions with the presence of melanised hyphae (phaeohyphomycosis), multifocal granulomatous hepatitis, perivascular lymphocytic infiltration, vacuolation of hepatocytes and vacuolation of the kidney tubule epithelium. No statistically significant differences were found in the survival of the fish with respect to experimental settings. The survival period ranged between 3 and 135 days.
Keywords: virulence; lymfocyty; Virulence; Animals; Erythrocytes; Mycoses; nemoci ryb; mykózy; Ascomycota; erytrocyty; Oncorhynchus mykiss; Fish Diseases; Lymphocytes; zvířata